Pemberdayaan Pasien Dengan Pendekatan Self Help Group Terhadap Perubahan Mekanisme Koping Pada Pasien Gangguan Jiwa Skizoprenia Di RSJD Dr Arif Z Surakarta - Endang Caturini Sulistyowati; Dwi Sulistyowati (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Schizophrenia is one of the most common forms of mental disorders in Indonesia. Effective treatments for mental disorders are coming from themselves (WHO, 2018), for some mental disorders require empowerment, one of which is Self Help Group therapy. Self Help Group aims to develop empathy among fellow group members where fellow group members provide mutual support to form adaptive coping. This study aims to determine the effect of empowering patients with the Self Help Group approach to coping mechanisms in patients with schizophrenic mental disorders. Method: The research is quasi-experiment with a pre-post test design with a control group design. Data were taken before and after the administration of self-help intervention groups in schizophrenia in the intervention group. The number of samples is 66 clients divided by 2, namely 33 respondents for the intervention group and 33 respondents for the control group. This study measured coping mechanisms. The research instrument used a coping mechanism questionnaire. Data were analyzed using a dependent t-test, independent multiple linear regression t-test. Results: The study proved that there are significant differences in the coping mechanism before and after giving the Self Help Group (p-value, 0.000). Self Help Group if implemented by the patient has the opportunity to improve coping mechanisms by 20.1% and is expected to improve the coping mechanism by 4.909 points. Conclusion: The Self Help Group used for interventions is considered effective to increase coping skills.